C.1 - Wilding, Norman; Laundy, Philip (London, 1958)
We hope we may be forgiven our temerity in producing this book in a relatively remote outpost of Empire, far removed from the fountainhead of parliamentary wisdom, but we can only plead that it represents the logical outcome of a richly rewarding occupation. The idea for this work came to us in the pursuit of our daily round. In the course of the researches which form a major part of a parliamentary librarian's duties we soon discovered that the answers to the wide range of inquiries which we dealt with relating to Parliament and its associated subjects involved the consultation of many volumes of varying scope and content. It was apparent that no single source of reference existed to which one could turn with such inquiries..
Keywords: Parliament